Source Credibility, Information Favorability, and Job Offer Acceptance - Fisher, Cynthia D.; Ilgen, Daniel R.; Hoyer, Wayne D. (Academy of Management Journal, 1979)
The impact of the favorability of information about a job and the source of information upon applicant perception of source credibility and upon job offer acceptance was examined. Results showed that interviewers are the least credible source and that giving negative job information enhanced source credibility but decreased job offer acceptance.